Legal support for the implementation of state agrarian policy in the context of sustainable regional development - Kuzmich, Iryna P. (Journal of the Belarusian State University. Law, 2021)
The article analyses the legal essence of the national concept of regional development in interrelation with the realisation of the state agrarian policy on the basis of research of legal support of sustainable development of rural territories and agrarian economy. The inconsistency of norms of current legislation in part of taking into account regional specifics when determining the conceptual and legal basis of socio-economic development of the state is noted. The classification of legal measures implemented within the framework of state agrarian policy, taking into account their impact on regional development, was proposed. The priorities of improving the agrarian legislation in the context of the adopted concept of sustainable development of regions were revealed.
Keywords: agrarian policy; agrarian legislation; state support; legal support; regional policy; regions; rural areas; agriculture; strategy; sustainable development